Analysis of glucocorticoid signalling by gene targeting1 - Reichardt, Holger Michael; Kaestner, Klaus; Wessely, Oliver; Gass, Peter; Schmid, Wolfgang; Schütz, Günther (The journal of steroid biochemistry and molecular biology, 1998)
Glucocorticoids are involved in the regulation of numerous physiological processes. The majority of these effects are thought to be mediated by the glucocorticoid receptor (GR) via activation and repression of gene expression. In most cases activation requires binding of a receptor-dimer to DNA while repression is mediated by protein-protein-interaction of GR-monomers with other transcription factors. To analyse the molecular mechanisms that underlie glucocorticoid effects, mouse mutations in the GR gene were generated and analysed. In order to address the role of glucocorticoid receptor signalling during development and in physiology, the gene was disrupted by gene targeting. Most of the mice homozygous for the mutation die shortly after birth due to severe lung atelectasis. Additional defects were found in the adrenals, liver, brain, bone marrow and thymus as well as in the feedback-regulation of the HPA-axis. To approach the question which functions of the GR are regulated by DNA-binding and which by protein-protein-interaction, a point mutation was introduced into the dimerization domain of the GR which is located in the DNA-binding domain. By homologous recombination in ES-cells using the Cre/loxP-system, mice carrying this mutation were generated [GR(dim) mice]. The mice are fully viable although they show impaired inducibility of gluconeogenetic enzymes in liver, defects in longterm renewal of erythroid progenitors and increased expression of POMC and ACTH in the pituitary. However neither in the lung nor the adrenals were any histological abnormalties found. In conclusion GR(dim)-mice represent a valuable tool to further analyse mechanisms of physiological effects of the GR.
Gesehen am 04.03.2025